Molecular characterization of NDM-1-producing carbapenem-resistant E. cloacae complex from a tertiary hospital in Chongqing, China - Hu, Kewang; Zhang, Jisheng; Zou, Jingbo; Zeng, Lingyi; Li, Jie; Wang, Jianmin; Long, Wenzhang; Zhang, Xiaoli (Frontiers in Cellular and Infection Microbiology, 2022)
Background: The aim of this study was to clarify the molecular characterisation of NDM-1-Producing carbapenem-resistant Enterobacter cloacae complex (CREL) at a teaching hospital in Chongqing, China. Methods: Antimicrobial susceptibility and resistance genes were analyzed. Epidemiological relationship was analyzed by Pulsed-field gel electrophoresis (PFGE) and Multilocus sequence typing (MLST). Conjugation experiments were performed to determine the transferability of plasmids. Whole-genome sequencing (WGS) of strains was implemented and the genetic environment of the blaNDM-1- and mcr-9-carrying plasmids were analyzed. Results: A total of 10 blaNDM-1-positive CREL isolates were identified. All isolates harbored multiple resistance genes. ECL68 and ECL78 co-producing blaNDM-1 and mcr-9. Among the four different sequence types (STs) detected, ST1466 was assigned as a novel ST. Six isolates exhibited highly similar PFGE patterns. Conjugation assay proved that all plasmids containing blaNDM-1 or mcr-9 could be transferred to recipients Escherichia coli.Whole genome sequencing indicated that blaNDM-1 genes were carried by diverse plasmids, including IncHI2/IncN, IncX3 and one unclassified plasmid type. The backbone structure of these plasmids involved in replication initiation (repAB), partitioning (parABM) and conjugation/type IV secretion (tra/virB). Analysis of the genetic environment showed that blaNDM-1 in three plasmids exhibited highly similiar structure with protype Tn125.Co-existence of blaNDM-1 and colistin resistance genes mcr-9 were detected in the two isolates, ECL68 and ECL78. In ECL68, blaNDM-1 and mcr-9 were present on the same plasmid while located in two separate plasmids in ECL78. The genetic environment of mcr-9 was organized as IS26-wbuC-mcr-9-IS903-pcoS-pcoE-rcnA-rcnR and two-component system encoding genes qseC and qseB were not found in two plasmids, which could explain mcr-9-harboring strains colistin susceptibility. Conclusions: We first report a nosocomial outbreak of NDM-1-producing E. cloacae complex ST177 in China. Conjugative plasmids are contributed to the horizontal transfer of antibiotic resistance genes. The prevalence even coexistence of blaNDM-1 and mcr-9 may further threaten public health.Our results highlight further surveillance for blaNDM-1 and mcr-9 is essential for prevent its dissemination.